Pollution of the Black Sea and its Study By Methods of Mathematical Modeling - Kordzadze, Avtandil A.; Demetrashvili, Demuri I. (Journals of Georgian Geophysical Society, 2017)
In this study, the articles devoted to simulation of dispersion processes of different substances in the seas and oceans are reviewed. The basic attention is focused on the diffusion mathematical models on spreading of substances of anthropogenic origin in the Black Sea. Numerical models developed at M. Nodia Institute of Geophysics (Tbilisi, Georgia) concerning distribution of different admixtures (oil, Strontium-90, Rioni River alluvium) in the Back Sea basin are described in more details. These models are based on nonstationary 2D and 3D transfer-diffusion equations using annual mean climatic flow field calculated by the barotropic and baroclinic models of the Black Sea dynamics. A theoretical method of determining the pollution source location in a water basin on known pollution concentrations in some points of the upper layer of the sea is also considered. The method is based on a conjugate transfer-diffusion equation. For solution of both the models of dynamics and admixture’s dispersion the two-cycle splitting methods, offered by G. I. Marchuk for solution of problems of atmosphere and ocean dynamics are used.